Design and performance testing of an axial-flow ventricular assist device developed at the Fu Wai Hospital in Beijing. - Zhang Y; Hu SS; Zhou JY; Sun HS; Zhang H; Zheng Z; Zhu XD; Li GR; Gui XM; Zhan Z; Jin DH; Zhang, Y; et al. (International Journal of Artificial Organs, 2008)
Purpose: Various ventricular assist devices (VADs) have been developed for clinical use in recent years. The aim of a multidisciplinary research team at the Fuwai Hospital of the Peking Union Medical College is to design and develop an axial flow left ventricular assist device (LVAD) for adults.Methods: Using Computational Fluid Dynamics (CFD), the inflow characteristics of the axial flow pump were analyzed. After CFD analysis, the axial pump was fabricated using a 5-axis, computer numerical control (CNC) milling machine. Performances of the pump both in vitro and in vivo were tested.Results: This VAD, which was developed after numerous CFD analyses for the flow characteristics of the pump, is 58.5 mm long, 30 mm wide and weighs 120 g. The pump can deliver 5 lpm for pressures of 100 mmHg over 8500 rpm. The NIH value was 0.01 g/100 L. The hemolysis, which was evaluated in an in vivo test, was a bit higher than the normal value, but remained within an acceptable range.Conclusions: Performance of the pump in vitro and in vivo was considered sufficient for an LVAD. Further design improvements are being undertaken in terms of hemolysis and thrombosis to improve the biocompatibility of the pump.